Local Government Autonomy and Democratic Governance in Bayelsa and Delta States - Gabriel Oromena Ezo (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study examined the effect of local government autonomy on community perceptions of local government effectiveness and community participation in governance in Bayelsa and Delta States. The study was guided by two research questions. A survey research design was adopted, and quantitative data were collected using structured questionnaires administered to local government staff, community leaders, and residents across selected local government areas in the two states. A total sample of 381 respondents was selected through stratified random sampling using the Taro Yamane formula. Data collected were analyzed using descriptive statistics such as frequencies, percentages, means, and standard deviations. Findings from the study revealed that local government autonomy has a positive effect on community perceptions of local government effectiveness. Respondents indicated that autonomy enhances planning, transparency, accountability, responsiveness, and service delivery, thereby improving public trust in local government institutions. However, the study also found that local government autonomy has not significantly improved community participation in governance, as most respondents reported low levels of citizen involvement in decision-making processes despite the existence of local government structures. The study concluded that while local government autonomy contributes to improved perceptions of effectiveness, its impact on community participation in governance remains weak in Bayelsa and Delta States. It was therefore recommended that government authorities should strengthen genuine local government autonomy by minimizing state interference in local council administration. In addition, local governments should institutionalize structured platforms for citizen participation, such as town hall meetings and participatory budgeting, to enhance grassroots engagement and democratic governance.